Same‐day colon capsule endoscopy is a viable means to assess unexplored colonic segments after incomplete colonoscopy in selected patients. Issue 10 (1st December 2018) - Hussey, Mary; Holleran, Grainne; Stack, Roisin; Moran, Neil; Tersaruolo, Claudio; McNamara, Deirdre
Abstract : Background: Same‐day colon capsule endoscopy (CCE) immediately following incomplete optical colonoscopy (OC) would have a number of advantages for patients, while also presenting unique procedural challenges including the effect of sedation on capsule propulsion and patient tolerance of protracted preparation and fasting. Aim: The aim of this article is to prospectively assess the efficacy of same‐day CCE after incomplete OC in an unselected patient cohort. Methods: This was an observational, prospective, single‐centre study of CCE post‐incomplete colonoscopies. Patients with an incomplete OC for any reason other than obstruction or inadequate bowel preparation were recruited. CCE was performed after a minimum of a one‐hour fast. Once the patient was fully alert, intravenous metoclopramide was administered after capsule ingestion when possible, and a standard CCE booster protocol was then followed. Relevant clinical information was recorded. CCE completion rates, findings and their impact, and adverse events were noted. Results: Fifty patients were recruited, mean age = 57 years and 66% ( n = 32) were female. Seventy‐six per cent ( n = 38) of CCEs were complete; however, full colonic views were obtained in 84% ( n = 42) of cases. Patients > 50 years of age were five times more likely to have an incomplete CCE and there was also a trend towards known comorbidities associated with hypomobility having reduced excretion rates. Overall diagnostic yield for CCE in the unexplored segments was 74% ( n = 37), with 26% ( n = 13) of patients requiring significant changes in management based on CCE findings. The overall incremental yield was 38%. CCE findings were normal 26% ( n = 13), polyps 38% ( n = 19), inflammation 22% ( n = 11), diverticular disease 25 ( n = 12), angiodysplasia 3% ( n = 1) and cancer 3% ( n = 1). Significant small bowel findings were found in three (6%) cases, including Crohn's disease and a neuroendocrine tumour. A major adverse event occurred in one patient (2%), related to capsule retention. Conclusion: Same‐day CCE is a viable alternative means to assess unexplored segments of the colon after incomplete OC in selected patients.